The Distribution of Pusako Randah Property in Minangkabau Society: Between Cultural Tradition and Islamic Law Provision - Nofialdi, Nofialdi; Rianti, Siska (Mazahib, 2024)
This article discusses the distribution of pusako randah property by the Minangkabau people. Pusako randah property is distributed when parents, as the property owner, are still alive and distributed only to daughters (daughter-based distribution). Whereas, according to the consensus of Tungku Tigo Sajarangan attended by ulama, ninik mamak, and intellectuals-scholar in 1952, the distribution of pusako randah property should be executed using farāid mechanism. Some data are obtained from in-depth interviews with six custom figures. The finding of this research reveals that the distribution of pusako randah property is not only executed after the death of parents but also divided before the parents’ death. Besides, pusako randah property is intended only for daughters, while sons do not have a right to inheritance property. Distribution agreement of assets while parents are still alive in Islam is categorized as a gift (hibah) to anticipate (sadd al-dzari'ah) potential property disputes after parents die. In the inheritance traditions of other Minangkabau people, the distribution agreement of assets when the parents are still alive while the transfer after the parents die could be categorized as a will distribution (waṣiah). However, the distribution still exceeds one-third of the total assets. The allocation of inheritance only to daughters is a tradition that deviates from the Tungku Tigo Sajarangan consensus, even though the aim is to realize a universal benefit. Keywords: Inheritance distribution, pusako randah property, Minangkabau